A Cationic Amphiphilic AIE Polymer for Mitochondrial Targeting and Imaging - Junliang Zhou; Haiyang Wang; Wen Wang; Zhiwei Ma; Zhenguo Chi; Siwei Liu (MDPI AG, 2022)
Mitochondria are important organelles that play key roles in generating the energy needed for life and in pathways such as apoptosis. Direct targeting of antitumor drugs, such as doxorubicin (DOX), to mitochondria into cells is an effective approach for cancer therapy and inducing cancer cell death. To achieve targeted and effective delivery of antitumor drugs to tumor cells, to enhance the therapeutic effect, and to reduce the side effects during the treatment, we prepared a cationic amphiphilic polymer with aggregation-induced emission (AIE) characteristic. The polymer could be localized to mitochondria with excellent organelle targeting, and it showed good mitochondrial targeting with low toxicity. The polymer could also self-assemble into doxorubicin-loaded micelles in phosphate buffer, with a particle size of about 4.3 nm, an encapsulation rate of 11.03%, and micelle drug loading that reached 0.49%. The results of in vitro cytotoxicity experiments showed that the optimal dosage was 2.0 μg/mL, which had better inhibitory effect on tumor cells and less biological toxicity on heathy cells. Therefore, the cationic amphiphilic polymer can partially replace expensive commercial mitochondrial targeting reagents, and it can be also used as a drug loading tool to directly target mitochondria in cells for corresponding therapeutic research.